1993
DOI: 10.1111/j.1476-5381.1993.tb13983.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sumatriptan on the cerebral intraparenchymal microcirculation in the cat

Abstract: 1 Sumatriptan, a 5-hydroxytryptamine (5-HT)1-like receptor agonist, is effective against the headache of migraine. The effects of sumatriptan injected via the carotid artery on the cerebral microcirculation were studied in 10 anaesthetized cats. 2 The local cerebral blood volume (CBV), mean transit time of blood (MTT) and cerebral blood flow (CBF) in the parieto-temporal cortex were measured by a photoelectric method. CBV represents the cumulative dimensions of the cerebral microvessels.3 Sumatriptan at 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Previous investigators (23–25) reported that sumatriptan did not alter CBF in the steady state. Perren et al (23) have shown that sumatriptan has a highly selective vasoconstrictor action on arteriovenous anastomoses within the cranial circulation of anaesthetized cats, but it does not modify CBF.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous investigators (23–25) reported that sumatriptan did not alter CBF in the steady state. Perren et al (23) have shown that sumatriptan has a highly selective vasoconstrictor action on arteriovenous anastomoses within the cranial circulation of anaesthetized cats, but it does not modify CBF.…”
Section: Discussionmentioning
confidence: 85%
“…Previous investigators (23–25) reported that sumatriptan did not alter CBF in the steady state. Perren et al.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Clinically effective treatments such as the 5‐HT 1B/1D receptor agonists, known as triptans, are supposed to derive their antimigraine benefit via inhibition of neuropeptide‐mediated activation of trigeminovascular afferents (Goadsby & Edvinsson, 1993) and vasoconstriction of the cerebral and meningeal vasculature (Humphrey & Feniuk, 1991; Moskowitz, 1993), but not the cerebral microcirculation ( Kobari et al , 1993 ). Of these two interlinked components, electrical or inflammatory mediated stimulation of rat trigeminal ganglia in vitro has been demonstrated to cause a significant release of the neuropeptide calcitonin gene‐related peptide (CGRP) from sensory nerve fibres, and a delayed synthesis and release of PGE 2 from dura mater ( Rich et al , 1996 ; Ebersberger et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Messungen des regionalen zerebralen Blutfiusses (rCBF) beim Menschen mittels SPECT (22,57) sowie dopplersonographische Messungen der Blutflufigeschwindigkeit(10,16,17,71) konnten keine oder nur wesentliche Anderungen dieser Parameter nach Gabe von Sumatriptan nachweisen. Auch tierexperimentell wurden, von den oben erwähnten vasokonstriktorischen Effekten abgesehen, keine Anderungen des rCBF oder des Blutvolumens festgestellt(40).Der für die Therapie von Migräne und Clusterkopfschmerz entscheidende Mechanismus scheint damit nicht primär auf der Anderung des zerebralen Blutfiusses bzw.…”
unclassified